PEMBELAJARAN AKUATIK BAGI SISWA PRASEKOLAH - Susanto, Ermawan (Jurnal Cakrawala Pendidikan, 2010)
Abstract Aquatic Learning for Preschoolers. This article discusses an appropriate and fun method in aquatic learning for preschoolers and provides a guideline to improve the process of aquatic learning for them. This article is based on literature on aquatic learning for preschoolers. The process of preschool aquatic learning deals with the development of children’s potentials through three aspects: basic psychomotor skill, basic attitude, and basic understanding. The basic psychomotor skill consists of: (1) water entry, (2) buoyancy, (3) leg action, (4) balance in the water, (5) arm action, and (6) breath control. The basic attitude consists of (1) bravery, (2) facility sharing, (3) respect for the rules, (4) attention to instructions, and (5) willingness to participate. The basic understanding consists of (1) class procedures, (2) swimming pool rules, (3) playing rules, (4) instruction language, and (5) mechanics. The aquatic learning program should also consider cognitive and affective aspects, besides the psychomotor aspect. Keywords: aquatic learning, preschool